Investigation of the logarithmic-KdV equation involving Mittag-Leffler type kernel with Atangana-Baleanu derivative - İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa; Baleanu, Dumitru (Elsevier, 2018)
This work presents analysis of the logarithmic-KdV equation involving new fractional operator called Atangana-Baleanu (AB) fractional derivative with Mittag-Leffler (ML) type kernel. The existence and uniqueness of the governing equation having AB fractional derivative with ML type kernel is proved with the aid of a fixed-point theorem. We present numerical simulations by using iterative algorithm. The effectiveness of various parameters and variables on the displacement are presented in Figures 1 and 2. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Fractional logarithmic-KdV equation; AB derivative; Fixed-point theorem; Existence and uniqueness; And numerical simulations